2017
DOI: 10.1016/j.jpha.2017.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Analytical techniques for serratiopeptidase: A review

Abstract: A review is presented on different analytical techniques used for qualitative and quantitative analysis of serratiopeptidase, a proteolytic enzyme, which has recently gained importance as an anti-inflammatory agent. Efforts have been made to collate all the relevant references to the extent possible. The review discusses the advantages and disadvantages of the cited analytical techniques, which will help to give insights into the methods used for estimation of serratiopeptidase as such, from clinical isolates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 28 publications
2
16
0
1
Order By: Relevance
“…The crude extract, ow-through, puri ed enzyme, induced cell extract; wild type strain cell extract was loaded in the SDS PAGE to check the molecular weight of the protein and to show the difference in protein expression and concentration [24]. The separating gel was 12% and the stacking gel was 5 % was used to perform the SDS PAGE.…”
Section: Sds Pagementioning
confidence: 99%
See 1 more Smart Citation
“…The crude extract, ow-through, puri ed enzyme, induced cell extract; wild type strain cell extract was loaded in the SDS PAGE to check the molecular weight of the protein and to show the difference in protein expression and concentration [24]. The separating gel was 12% and the stacking gel was 5 % was used to perform the SDS PAGE.…”
Section: Sds Pagementioning
confidence: 99%
“…The puri ed sonicated sample and supernatant was loaded in the casein plate. The plate was incubated at 37°C for 16 hours and checked for the zone clearance at patched sites [24].…”
Section: Caseinolytic Assaymentioning
confidence: 99%
“…Numerous studies have been carried out for quantitative and qualitative estimation of SER [12]. Thin-layer chromatography [13], SDS-PAGE gel electrophoresis [14], and X-ray powder diffractometry [15] are some of the techniques reported for successful qualitative estimation of SER.…”
Section: Manasi Et Almentioning
confidence: 99%
“…Thin-layer chromatography [13], SDS-PAGE gel electrophoresis [14], and X-ray powder diffractometry [15] are some of the techniques reported for successful qualitative estimation of SER. Quantitative instrumental methods use chromatography, field flow fractionation, electrophoresis, etc., for separation, and physical properties such as absorption, fluorescence, conductivity, and light scattering are used to measure the analyte accurately and precisely [12]. For quantitative analysis, caseinolytic assay method [16][17][18][19][20][21][22][23][24][25][26][27], spectroscopy [28][29][30][31][32][33][34][35], fluorescence spectrometry [36], enzyme-linked immunosorbent assay (ELISA) [37][38][39], radioimmunoassay [40], ultraviolet (UV) microplate method [41], high-performance LC (HPLC) [42], and LC-MS method [43] are reported.…”
Section: Manasi Et Almentioning
confidence: 99%
“…The enzyme has an EC number 3.4.24.40 and belongs to the group Serralysin. It is originally obtained from Serratia marcescens isolated from the intestine of the silkworm Bombyx mori L. Extensive review on analytical techniques used in the qualitative and quantitative analysis of serratiopeptidase has been published by [ 3 ], where the authors pointed out a need for selective and specific techniques for the quantification of serratiopeptidase. A detailed review of existing evidences for serratiopeptidase has been reported by [ 4 ].…”
Section: Introductionmentioning
confidence: 99%